2021
DOI: 10.1039/d1gc00171j
|View full text |Cite
|
Sign up to set email alerts
|

Electrooxidative tandem cyclization of N-propargylanilines with sulfinic acids for rapid access to 3-arylsulfonylquinoline derivatives

Abstract: An environmentally friendly electrochemical protocol for tandem cyclization has been developed, which offers a rapid access to structurally diverse functional 3-arylsulfonylquinoline derivatives. Under undivided electrolysis conditions, the reactions of N-propargylanilines...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Later, Zhang and co-workers developed a visible-light-induced strategy for a similar synthesis, using iodine­(III) reagent as an aryl source and DABSO as a sulfur dioxide source (Figure c) . Recently, the Wang group reported the synthesis of 3-arylsulfonylquinolines from aryl sulfinic acid using the electro-oxidation technique . In this study, we have shown that the aryl diazonium tetrafluoroborate and DABSO reacted with N -propargylanilines under ambient conditions to afford 3-arylsulfonylquinolines in the absence of any external additives or catalysts (Figure a).…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Later, Zhang and co-workers developed a visible-light-induced strategy for a similar synthesis, using iodine­(III) reagent as an aryl source and DABSO as a sulfur dioxide source (Figure c) . Recently, the Wang group reported the synthesis of 3-arylsulfonylquinolines from aryl sulfinic acid using the electro-oxidation technique . In this study, we have shown that the aryl diazonium tetrafluoroborate and DABSO reacted with N -propargylanilines under ambient conditions to afford 3-arylsulfonylquinolines in the absence of any external additives or catalysts (Figure a).…”
Section: Introductionmentioning
confidence: 77%
“…37 Recently, the Wang group reported the synthesis of 3-arylsulfonylquinolines from aryl sulfinic acid using the electro-oxidation technique. 39 In this study, we have shown that the aryl diazonium tetrafluoroborate and DABSO reacted with N-propargylanilines under ambient conditions to afford 3-arylsulfonylquinolines in the absence of any external additives or catalysts (Figure 1a).…”
Section: ■ Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…13 Moreover, Wang and co-workers presented an effective protocol to afford 3-arylsulfonylquinoline derivatives via electrooxidative tandem cyclization of N -propargylanilines with sulfinic acids. 14 To the best of our knowledge, the electrochemical approaches for forming 2,3-disubstituted quinolines still remain challenging and have thus far not yet been reported. As part of our continuous interest in electrochemical synthesis and green chemistry, 15 we herein report an effective electrochemical intramolecular annulation protocol to synthesize such important sulfonylated skeletons by treating phenylethynylbenzoxazinanones with sulfonyl hydrazides in an undivided cell under mild conditions (Scheme 1c).…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these methods suffer from limitations such as the requirement of acidic or basic reaction conditions, which are incompatible with sensitive functionalities. Over the past few years, numerous transition-metal-catalyzed domino cascade reactions to form the quinoline ring system have been developed. Considering their synthetic and pharmaceutical importance, there is a high demand to develop an innovative methodology for the construction of functionalized quinoline-containing structures.…”
mentioning
confidence: 99%